Rediscovery of Choroterpes atramentum in Costa Rica, type species of Tikuna new genus (Ephemeroptera: Leptophlebiidae: Atalophlebiinae), and its role in the "Great American Inter-change" - Savage, Harry M.; Flowers, R. Wills; V., Wendy Porras (Zootaxa, 2005)
A new genus, Tikuna, is described based on recent collections of adults and nymphs of Choroterpes atramentum Traver from western Costa Rica. All recent collections are from streams on or near the Nicoya Complex, the oldest geological formation in Lower Central America. Tikuna belongs to a lineage of South American Atalophlebiinae (Leptophlebiidae: Ephemeroptera) whose origin is hypothesized to have been in the late Cretaceous–early Tertiary. Some implications of the distribution of Tikuna for theories on the origin of Costa Rica’s biota are discussed.